Traditional Music in Modern Java Gamelan in a Changing Society - Becker, Judith (University of Hawai'i Press, 1980)
Musicologist Judith Becker contends that sociopolitical changes in Javanese society since the 1940s are reflected in changes in the structure of gamelan music, which is one of the traditional musics of Java. She sees gamelan music as a musical system in a state of crisis, unsure of its proper function and direction. While traditional gamelan musical structures supported old Hindu-Javanese concepts of cosmology and kingship, modern innovations reflect Indonesian nationalism and a desire to become a "twentieth century nation." In particular, the introduction of Western musical notation, which Becker describes as "the most pervasive, penetrating, and ultimately the most insidious type of Western influence," is changing gamelan from an aural to a written tradition. Becker examines the works of contemporary composers Ki Wasitodipuro and Ki Nartosabdho to illustrate modern innovations in gamelan compositions and the attitudes of composers to their music, as they attempt to compromise between the ethos and structure of traditional gamelan music and the changing tastes and attitudes of the modern Indonesian nation. In addition to her interpretation of the political influence on gamelan music, Becker includes four appendices that ethnomusicologists will find valuable. Appendix I articulates her theory of the derivation of central Javanese gamelan gongan, the basic temporal/melodic repeated unit of gamelan music. Appendix II gives biographical sketches of Ki Wasitodipuro and Ki Nartosabdho and lists their compositions referred to in the text. Appendices II and IV deal with various aspects of pathet, a Javanese system of classifying gamelan pieces. A fifth appendix, by Alan R. Templeton, gives an informational analysis of pathet.